KEKUATAN SUMBER DAYA MANUSIA DALAM MEMASARKAN PRODUK DAN DAMPAKNYA PADA KINERJA KARYAWAN ASURANSI JIWA DI PROVINSI KEPULAUAN RIAU - Suhardi, Suhardi; Syaifullah, Syaifullah (Jurnal Benefita, 2017)
The significance of life insurance products is not dependent on technological sophistication and the equipment used, but rather on the service of its Human Resources-based officers, therefore this research wants to see the strength of human resources in marketing the products and their impact on the performance of life insurance employees in the Province Riau Islands, so the purpose of this research is to know the influence of the power of human resources which variables in particular are work motivation, competence, work environment, compensation for organizational citizenship behavior (OCB) and performance of life insurance officer in Riau Islands Province. The sample of this research is 206 respondents with multystage sampling method and purposive sampling design. Data were collected using questionnaire with Likert scale and then analyzed with Structural Equation Modeling (SEM) through AMOS version 21 program. The result of analysis proved that the competence and work environment had no significant effect on the performance, and the competence also had no significant effect on organizational citizenship behavior (OCB). Significant effects in this study were: Work motivation for organizational citizenship behavior (OCB), work environment for organizational citizenship behavior (OCB), compensation for organizational citizenship behavior (OCB), work motivation on performance, compensation for performance, and organizational citizenship behavior (OCB) on performance.